PERAN DPD RI TERHADAP PEMBANGUNAN DAERAH PERBATASAN DAN TERTINGGAL DALAM ERA OTONOMI DAERAH - Gusman, Erry (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
The construction of border regions and disadvantaged areas is one of President Jokowi's and Vice President Jusuf Kalla's Nawacita program. Each region does not have to be exactly the same in carrying out development, differences in development need to be done in order to accommodate the characteristics and capabilities of each region. The term is asymmetric decentralization. This research itself is to support the Draft Law on the Acceleration of the Development of Disadvantaged Regions which is being drafted by the DPD RI. Although the government has issued various policies to catch up, but to realize the acceleration of underdeveloped regional development a strategic legal umbrella is needed. The formulation of the problems raised in this study are: 1) how to realize the acceleration of border area development and lag behind through meeting basic needs such as education, health, food, infrastructure? 2) how to synergize the implementation of these programs to reduce inequality between regions? This research will use normative juridical research and supported by empirical juridical research so that it will be able to see the realization of the acceleration of border area development and lagging through meeting basic needs such as education, health, food, and infrastructure are important in building regional development equality in Indonesia. To realize this, food needs to synergize the implementation of these programs to reduce inequality between regions in Indonesia.